Utilização de complexo enzimático em dietas para codornas de corte - Iwahashi, Alexandre Shigueki (2009)
Three experiments w ere carried out to evaluate the effects of enzymatic supplementation on meat type quails performance during the initial (1 - 14d) and growing (15 - 35d) phases and nutrients metabolisation . In the first experiment, were used, 1,400 meat type quails, one day ag e, non - sexed, allotted in a completely randomized design, with eight treatments and five replications with 35 birds per replication. All the diets were based on corn and soybean meal. The treatments used were: a positive control (PC) formulated to meet the nutritional requirements of this growth phase; a positive control supplemented with enzymatic complex (PC+EC); two negative controls supplemented with EC and reduced in 2 and 4% (60 and 120 kcal/kg) on metabolizable energy (NC 2 and 4% ME); two NC supplem ented with EC and reduced contents of amino acids: lysine, methyonine + cystine and threonine (NC 2 and 4% AA's); two NC supplemented with EC and combined reductions on ME and AA's (NC 2 and 4% ME+AA's). There were no differences (P<0.05) in body weight, w eight gain and feed conversion ratio between treatments. In treatment NC 4% ME+ AA's was observed increase in feed intake compared to PC and PC+EC. The enzymatic supplementation (xylanase and β - glucanase) can be used efficiently in corn soybean meal diets without performance losses to meat type quails from 1 to 14 days of age. To the second e xperiment were used 960 meat type quails distributed in a completely randomized design, eight treatments and five replications with 24 birds per replication. The treatments used were the same of first trial and the experimental diets were based on nutritio nal requirements for this phase (15 - 35d). There were no differences (P>0.05) in feed intake, feed conversion ratio and carcass traits between treatments. Supplementation "on top" (PC+EC) decreased the weight gain (P<0.05) compared to P C . The enzyme complex was effective in maintain the weight gain among the groups, except between NC 2% ME and 4% ME+AA's, being lower for the last. In conclusion, the supplementation can be used successfully in diets reduced by 120.0 kcal/kg of ME or 4% in the AA's contents fo r meat type quails from 15 to 35 days of age. It's economically advantageous to supplement diets reduced on AA's contents instead of ME. In third experiment, a metabolis m trial, 160 meat type quails were distributed in a completely randomized design with e ight treatments, four replication and 5 birds per replication. The treatments were the same to performance trial. There were no differences (P>0.05) in metabolisable coefficients of dry matter, organic matter, crude protein and gross energy between treatme nts. The metabolisation coefficient of NDF was improved (P<0.05) by enzyme supplementation. The economic analysis demonstrate advantages (P<0.05) on AA's reductions instead ME.